Detailed heat transfer measurements in a model of an integrally cast cooling passage - Ieronymidis, I; Gillespie, D; Ireland, P; Kingston, R; ASME (2006)
Detailed measurements of the heat transfer coefficient distributions on the internal surfaces of a novel gas turbine blade cooling configuration were carried out using a transient liquid crystal technique. The cooling geometry, in which a series of racetrack passages are connected to a central plenum, provides high heat transfer coefficients in regions of the blade in good thermal contact with the outer blade surface. The Reynolds number changes along its length because of the ejection of fluid through a series of 19 transfer holes in a staggered arrangement, which are used to connect ceramic cores during the casting process. Heat transfer coefficient distributions on this holes surface are particularly important in the prediction of blade life, as are heat transfer coefficients within the hole. Results at passage inlet Reynolds numbers of 21667, 45596 and 69959 are presented along with in-hole htc distributions at Rehole = 5930, 12479, 19147 and suction ratios of 0.98, 1.31, 2.08, 18.67. All values are engine representative. The results were compared to predictions made using the commercial CFD package Fluent. Characteristic regions of high heat transfer downstream of the transfer holes were observed with enhancement of up to 92 % over the Dittus-Boelter level. Within the transfer holes, the average htc level was strongly affected by the crossflow at the hole entrance. Htc levels were low in these short (l/d = 1.5) holes fed from regions of developed boundary layer. Copyright © 2006 by ASME.